(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Adverse Drug Reactions (ADRs) are global problem of major concern. Spontaneous reporting of ADRs is the cornerstone of pharmacovigilance. However, underreporting is a huge problem due to lack of reporting culture among healthcare professionals. Objectives: the purpose of the present study was to assess the knowledge, attitude and practice of physicians regarding reporting of ADRs, and pharmacovigilance as well as to identify the reasons for under-reporting with suggestion for improvement in the reporting system. Methodology: This cross sectional, observational study was conducted to assess the knowledge, attitudes and practices regarding adverse drug reaction reporting among physicians working in different level hospitals of Bangladesh. Data were collected from 308 physicians during the period of January to December 2012 using structured questionnaire. Result: Response rate was 97%. Majority of the respondent (95%) felt that ADR reporting is necessary and it is a professional obligation. Inadequate knowledge of reporting mechanism, unavailability of reporting form, complex reporting system, lack of time and inadequate expertise were the main reasons cited for underreporting. Majority of the respondents suggested regular training sessions, strengthening the drug administration department, government law, regular follow up and inclusion of ADR reporting exercise in undergraduate and post graduate curriculum may help to improve the situation. Conclusion: The deficiency of knowledge, attitude and practice of physician regarding ADR reporting need urgent attention on priority basis not only for the success of pharmacovigilance program but also for better clinical management of the patient in general. J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 18-22